The potential of leaf extract of Barleria lupulina for detoxification of aflatoxins - and R. VELAZHAHAN*, K. KANNAN (Indian Phytopathology, 2014)
The fungi Aspergillus flavus and A. parasiticus which often contaminate foods and feeds produce aflatoxin, a secondary metabolite and the most potent naturally occurring carcinogen known. Aflatoxins are highly stable molecules which are extremely difficult to remove or destroy once formed in a commodity. In the present study we explored the potential of some indigenous medicinal plants in the detoxification of aflatoxins in vitro. Of the various plant extracts tested, methanolic extract (1%) obtained from leaves of Barleria lupulina Lindl. showed maximum degradation of aflatoxin B1. The methanol extract of B. lupulina also showed significant levels of detoxification of other aflatoxins tested viz., AFB2, AFG1 and AFG2. Maximum detoxification occurred at pH 10, whereas the percentage detoxification decreased at pH 7 and pH 3. Time course study of aflatoxin detoxification by B. lupulina extract showed that degradation of aflatoxin occurred within 10 min and the percentage of degradation gradually increased with increase in incubation time.